Relationship Between Serum Zinc, Iron and Copper Level and Apoptosis in Human Gastric Mucosa: A Cross-Sectional Study - Alipour, Beitullah; Ghaffari, Aida; Ostadrahimi, Alireza; Safaiyan, Abdolrasoul; Modaresi, Jabiz; Mehrabany, Elnaz Vaghef (Pakistan Journal of Nutrition, 2011)
Gastric cancer is the fourth most common malignancy and the second leading cause of mortality among cancer patients in the world. Nutritional and epidemiological studies have indicated that zinc, iron and copper status modulates the risk of developing cancer and on the other hand, apoptosis has been reported to play a decisive role in precancerous changes. The aim of this cross-sectional study was to investigate whether there is any relationship between serum zinc, iron and copper levels and apoptosis (as an early indicator of gastric cancer changes) in human gastric mucosa. This cross-sectional study was conducted on 62 subjects with over 18 years of age, referred to 2 hospitals (Shahid Madani and Imam Reza hospitals) in Tabriz, Iran between October and December 2008 to undergo an upper gastrointestinal endoscopy. Serum levels of zinc, iron and copper were measured by atomic absorption spectroscopy and apoptosis was detected by TUNEL technique. Stepwise regression was exploited to access the relationship between apoptosis rate and serum zinc, iron and copper levels. Mean number of apoptotic (TUNEL positive) cells, serum zinc, iron and copper levels were 2.15±0.22, 111.47±2.18 (μg/dl), 145.20±5.24 (μg/dl) and 137.52±3.04 (μg/dl) respectively. The present study found no relationship between the rate of apoptosis and baseline serum levels of neither of zinc, iron and copper. Our study showed that serum zinc, iron and copper levels didn’t affect apoptosis in human gastric mucosa. It is suggested that more interventional and controlled studies be done.